Controlled synthesis of O-glycopolypeptide polymers and their molecular recognition by lectins - Pati, Debasis; Shaikh, Ashif Y.; Das, Soumen; Nareddy, Pavan Kumar; Swamy, Musti J.; Hotha, Srinivas; Sen Gupta, Sayam (Biomacromolecules, 2012)
The facile synthesis of high molecular weight water-soluble O-glycopolypeptide polymers by the ring-opening polymerization of their corresponding N-carboxyanhydride (NCA) in very high yield (overall yield > 70%) is reported. The per-acetylated-O-glycosylated lysine-NCA monomers, synthesized using stable glycosyl donors and a commercially available protected amino acid in very high yield, was polymerized using commercially available amine initiators. The synthesized water-soluble glycopolypeptides were found to be alpha-helical in aqueous solution. However, we were able to control the secondary conformation of the glycopolypeptides (alpha-helix vs nonhelical structures) by polymerizing raceznic amino acid glyco NCAs. We have also investigated the binding of the glycopolypeptide poly(alpha-manno-O-lys) with the lectin Con-A using precipitation and hemagglutination assays as well as by isothermal titration calorimetry (ITC). The ITC results clearly show that the binding process is enthalpy driven for both alpha-helical and nonhelical structures, with negative entropic contribution. Binding stoichiometry for the glycopolypeptide poly(alpha-manno-O-lys) having a nonhelical structure was slightly higher as compared to the corresponding polypeptide which adopted an alpha-helical structure.

Cationic charged helical glycopolypeptide using ring opening polymerization of 6-deoxy-6-azido-glyco-N-carboxyanhydride - Shaikh, Ashif Y.; Das, Soumen; Pati, Debasis; Dhaware, Vinita; Sen Gupta, Sayam; Hotha, Srinivas (Biomacromolecules, 2014)
Glycopolypeptides with a defined secondary structure are of significance in understanding biological phenomena. Synthetic glycopolypeptides, or polypeptides featuring pendant carbohydrate moieties, have been of particular interest in the field of tissue engineering and drug delivery. In this work, we have synthesized charged water-soluble glycopolypeptides that adopt a helical conformation in water. This was carried out by the synthesis of a glyco-N-carboxyanhydride (glyco-NCA) containing an azide group at the sixth position of the carbohydrate ring. Subsequently, the NCA was polymerized to obtain azide-containing glycopolypeptides having good control over molecular weight and polydispersity index (PDI) in high yields. We were also able to control the incorporation of the azide group by synthesizing random co-glycopolypeptide containing 6-deoxy-6-azido and regular 6-OAc functionalized glucose. This azide functionality allows for the easy attachment of a bioactive group, which could potentially enhance the biological activity of the glycopolypeptide. We were able to obtain water-soluble charged glycopolypeptides by both reducing the azide groups into amines and using CuAAC with propargylamine. These charged glycopolypeptides were shown to have a helical conformation in water. Preliminary studies showed that these charged glycopolypeptides showed good biocompatibility and were efficiently taken up by HepG2 cells.

Controlled synthesis of end-functionalized mannose-6-phosphate glycopolypeptides for lysosome targeting - Das, Soumen; Parekh, Nimisha; Mondal, Basudeb; Sen Gupta, Sayam (ACS Macro Letters, 2016)
The ubiquitous expression of the mannose-6-phosphate receptor on the majority of human cells makes it a valid target in the quest to deliver therapeutics selectively to the lysosome. In this work end-functionalized polyvalent mannose-6-phosphate glycopolypeptides (M6P-GPs) with high molecular weights (up to 22 kDa) have been synthesized via NCA polymerization. These synthetic M6P-GPs were found to display minimal toxicity to cells in vitro and show exceptional selectivity for trafficking into lysosomes in various cell lines. Comparison of the cellular uptake behavior of M6P-GP and the corresponding mannose-GP polymer reveals that incorporation of the phosphate moiety at the 6-position of mannose completely alters its trafficking behavior and becomes exclusively lysosome specific. We also demonstrate that trafficking of M6P-GPs in mammalian cells is likely associated with the CI-MPR receptor pathway.